La percezione e la mente senza coscienza - Gatti, Maria Gabriella; Fargnoli, Domenico (Il sogno della farfalla, 2022)
Philosophers and psychiatrists have long investigated the concept of perception and the relationship between sensible experience and its mental elaboration. In this article the authors analyze how the theoretical elaborations centered on the connection between perception and consciousness have greatly influenced psychopathology and the approach to mental illness and psychotherapy. The human birth theory formulated by Massimo Fagioli has thoroughly explained the rapport between perception and pulsional and non-conscious dynamics. This theory has opened a new perspective for the comprehension of mental states such as the perception-phantasy, fundamental in the psychotherapeutic relationship.